The Effect of Work Engagement On Organizational Silence: The Case Of Civil Servants - Aksoy, Yeşim; Özler, Nezire Derya Ergun (Fırat Üniversitesi, 2023)
Job engagement, defined as the dedication of employees to their work with the highest performance, is a very important concept for organizations. Job engagement consists of three dimensions: energy, dedication, and concentration. Organizational silence, on the other hand, can be defined as employees knowingly and willingly not expressing their opinions and thoughts in the face of an incident in the organization. As the job engagement of employees increases organizational silence will decrease in return individuals express their ideas freely. Organizational silence consists of three dimensions as acquiescent, defensive, and protective silence. The aim of this study is to determine the effect of work engagement on organizational silence. For this purpose, data were collected on a voluntary basis from civil servants working in a municipality operating in Ankara. The regression analysis showed that work engagement has a positive effect on organizational silence; energy and concentration dimensions of work engagement had no significant effect on acquiescent, defensive, and protective silence; dedication, a dimension of work engagement, has a significant effect on acquiescent and defensive silence but not on protective silence.

İşgörenlerin yaptıkları işe en yüksek performans ile kendilerini vermeleri olarak tanımlanan işe adanmışlık örgütler için çok önemli bir kavramdır. İşe adanmışlık enerjiklik, adanma ve konsantrasyon boyutlarından oluşmaktadır. Örgütsel sessizlik ise çalışanların örgüt içerisindeki bir olay karşısında görüş ve düşüncelerini bilerek ve isteyerek belirtmemeleri olarak tanımlanmaktadır. Çalışanların işe adanmışlık düzeyleri arttıkça örgütsel sessizlik azalmakta, bireyler fikirlerini özgür bir şekilde ifade etmektedir. Örgütsel sessizlik kabullenici, korunmacı ve korumacı sessizlik olmak üzere üç boyuttan oluşmaktadır. Bu çalışmanın amacı işe adanmışlığın örgütsel sessizlik üzerindeki etkisini belirlemektir. Bu amaçla Ankara ilinde faaliyet gösteren bir belediyede görev alan çalışanlardan gönüllülük esasına göre veriler toplanmıştır. Yapılan regresyon analizi sonucunda işe adanmışlığın örgütsel sessizlik üzerinde pozitif yönde bir etkisinin bulunduğu; enerjiklik ve konsantrasyonun kabullenici sessizlik, korunmacı sessizlik ve korumacı sessizlik üzerinde anlamlı bir etkisinin olmadığı; adanmanın örgütsel sessizlik boyutlarından kabullenici sessizlik ve korunmacı sessizlik üzerinde anlamlı bir etkisinin olduğu, korumacı sessizlik üzerinde ise anlamlı bir etkisinin olmadığı görülmüştür.
İŞE ADANMIŞLIĞIN ÖRGÜTSEL SESSİZLİK ÜZERİNDEKİ ETKİSİ: KAMU ÇALIŞANLARI ÖRNEĞİ